Efek Slot Pada Antena Mikrostrip Hexangular Dual Band Dengan Antena Awal 2,4 Ghz - Shafwan, Almas; Aritonang, Sovian; Murniati, Riri (Rekayasa Material, Manufaktur dan Energi, 2024)
Microstrip antennas play a crucial role in modern communication technology, with their performance dependent on shape and size. This study explores the impact of adding slots to hexagonal microstrip antenna radiation areas. The hexagonal shape was chosen due to its underexplored potential for slot additions. Slots act as elements influencing antenna radiation performance and altering characteristics. The research investigates the effects of various slot shapes and sizes (each with an area of 4 ) on hexagonal microstrip antennas at the initial frequency of 2.4 GHz. The importance of this study lies in the selected initial frequency, aligning with the micro-wave spectrum commonly used in wireless communication, radar, and telecommunications equipment. The hexagonal microstrip antenna, popular for its compact and efficient design, is relevant to modern communication devices.